PENENTUAN KLORAMFENIKOL DALAM DAGING AYAM BROILER DENGAN METODE HIGH PERFORMANCE LIQUID CHROMATOGRAPHY - Aman Sentosa Panggabean (JURNAL KIMIA MULAWARMAN, 2012)
Determination of chloramphenicol on broiler meat in traditional market by using High Performance Liquid Chromatography (HPLC) method has been done. The optimal of result determination to obtain, the HPLC system has been optimalized for the important parameters are composition of mobile phase, injection sample volume, flow rate and eluen pH. The result of research shown that the optimum conditions to obtain from the research are composition of mobile phase methanol:water (80:20), injection sample volume 5 µL, flow rate 0.5 mL/minute and eluent pH are 6 has been achieved. The analytical performance of method has been optimalized and gives good performance which shown with reproducibility of this method as coefficient of variation percentage (% CV) was 0.2198%, limit of detection was 0.1051 mg/L, and % recovery for the chicken meat sampel with 3 different samples > 95%. This result showed this method capable to application for the routine analysis of the determination chloramphenicol countent in samples.Keywords: Chloramphenicol, HPLC, Analytical performance, Broiler Meat